Pulmonary Embolism and Chronic Obstructive Pulmonary Disease - Bertoletti, Laurent; Couturaud, Francis; Sanchez, Olivier; Jimenez, David (Seminars in Thrombosis and Hemostasis, 2022)
Chronic obstructive pulmonary disease (COPD) is a frequent and devastating chronic respiratory disease. COPD is ranked among the top five causes of death worldwide. Patients with COPD suffer from persistent dyspnea, with periods of acute worsening, called exacerbations. Such exacerbations may be severe. In fact, one-third of COPD patients will be hospitalized because of an exacerbation. Hospitalization due to respiratory failure has been identified as a powerful predisposing risk factor for venous thromboembolism (VTE) for many years. Therefore, COPD is recognized as a moderate risk factor for VTE, with an odds ratio between 2 and 9, similar to other risk factors such as estrogen-containing contraceptives or (any) cancer. However, unlike other risk factors such as contraception, the presence of COPD can modify the initial presentation of VTE and worsen the short-term prognosis of patients who have acute pulmonary embolism (PE), particularly during a COPD exacerbation. It is not only that both stable COPD and acute exacerbations of COPD might increase the risk of VTE, but PE itself may mimic the symptoms of a COPD exacerbation. Hence, some authors have evaluated the prevalence of PE among COPD patients with acute worsening. This clinical review (1) gives an update on epidemiological data, clinical presentation, and prognosis of PE associated with COPD; (2) presents the results of the Prevalence de l'Embolie Pulmonaire chez les patients admis pour exacerbation de BPCO study, which aimed at determining the frequency of PE in COPD patients hospitalized for an acute exacerbation; (3) discusses the results of the Significance of Pulmonary Embolism in COPD Exacerbations study, the first randomized trial having compared the efficacy of a systematic search for PE versus routine care on admission for a COPD exacerbation; and (4) provides a selection of remaining unmet needs on the association between COPD and PE.
Keywords: pulmonary embolism; chronic obstructive pulmonary disease; anticoagulation; venous thromboembolism; diagnosis